Implementation of Multimedia Autoplay-Based Communication Media in Science Learning - Mudir, Syamsul; Sukmarini, Andi Vita; Yusmanizar, Yusmanizar (Journal of Education Review Provision, 2025)
The Application of Multimedia Autoplay-Based Communication Media in Science Learning at SMAN 3 Penajam Paser Utara (supervised by Andi Vita Sukmarini and Yusmanizar) Audiovisual multimedia autoplay-based instructional media is one form of technological advancement in learning. In its use, teachers can present text, images or videos, graphics, maps, and other materials not available in textbooks in an engaging format to attract students' attention to the learning process. This study is qualitative research employing a phenomenological approach. The data were collected through observation, interviews, and documentation. The researcher used a flow model analysis which involves several stages: data collection, data reduction, data presentation, and conclusion drawing, based on empirical information from SMAN 3 Penajam Paser Utara. The results of the study show that the implementation of multimedia autoplay-based communication media in science learning at SMAN 3 Penajam Paser Utara was carried out in three stages: design (developing multimedia autoplay-based teaching media), implementation (classroom teaching and learning activities), and evaluation (receiving feedback from students). The challenges encountered in using this media include a lack of understanding and skills in creating learning materials, the difficulty of accessing free applications to support media development, and technical obstacles such as electricity and internet connectivity.